Applying discipline character: Parents vs. teachers - Wenti Aprianti; Heri Yusuf Muslihin; Elan Elan (Universitas Ahmad Dahlan, 2021)
Disciplining preschool-aged children is pivotal since it helps parents to introduce rules and basis to face challenges in life. Students in RA Baiturrahman Tasikmalaya tend to exhibit a discipline attitude. The present study aimed to investigate how studentsâ€™ parents and children applied discipline character. To this end, a qualitative descriptive method was applied. The participants of the study were recruited using proportional sampling technique. The data were collected through observation and interviews. The obtained data were analyzed. The data analysis process includes data collection, data reduction, data presentation, and drawing of conclusion.Â The result of the study revealed that parents and teachers implemented conditioning and modeling to internalize the character. In the school setting, teacher internalize the character based on Islamic values in a structured manner.